Relationship between insulin resistance and adipocytokines: the mediator role of adiposity in children - Caroline Brand; Adroaldo Cezar Araujo Gaya; Arieli Fernandes Dias; Cesar Agostinis-Sobrinho; Juliano Boufleur Farinha; Francesco Pinto Boeno; Jorge Mota; Alvaro Reischak de Oliveira; Anelise Reis Gaya (Taylor & Francis Group, 2020)
Background: Leptin and adiponectin interact with each other in the modulation of obesity and insulin resistance (IR) and it is also important to consider the role of cardiorespiratory and muscular fitness in these relationships. Aim: To analyse the relationship between IR with adipocytokines in children, and to test the mediation effect of %BF (percentage of body fat) in the association of IR with leptin, adiponectin, and L/A ratio. Subjects and methods: This cross-sectional study comprised a sample of 150 schoolchildren, aged 6-11 years, from school in Porto Alegre, Brazil. The following variables were evaluated: cardiorespiratory fitness (CRF), muscular fitness (MF), percentage of body fat (%BF), and biochemical variables (leptin, adiponectin, glucose, and insulin). Results: IR was associated with leptin and L/A ratio, after adjustments for age, sex, sexual maturation, and CRF. When adjusted for age, sex, sexual maturation, and MF, an association was found between IR with leptin and L/A ratio. Moreover, %BF was a mediator in the association between IR and leptin, as well as IR and L/A ratio, explaining 54% and 57% of these associations, respectively. Conclusion: Leptin and L/A ratio are positively associated with IR after adjustments. Also, %BF is a mediator in the associations between IR and leptin and L/A ratio.